Experimental study on the performance of water-less floor heating and hot water dual supply air source heat pump system - NIU Jianhui; AN Zelong; ZHANG Chenyang; WU Yuzhou; ZHANG Yujin (Zhileng xuebao, 2025)
A new type of air source heat pump system combined waterless floor heating and hot water supply was proposed, which is characterized in that the refrigerant is condensed directly in the buried pipe for floor heating, at the same time, the high temperature refrigerant is exchanged in the outer coil water heater to produce domestic hot water. The prototype was processed and tested in three modes: single floor heating, two combined supply and single water heater. The experimental results show that the surface temperature of the floor is maintained between 25 ℃ and 33 ℃, and the air temperature is maintained between 18 ℃ and 22 ℃ whether in the sole floor heating mode, dual supply mode, or single water heater mode. Due to the heat storage effect of the capillary floor, the air temperature in the room remained above 18 ℃ within 113~245 min of stopping heating to the room. When the ambient temperature is -5 ℃, after 572.3 min, the water temperature of the water heater rose to 45 ℃; The minimum system heating capacity and EER can reach to 2.70 kW and 3.55, respectively.